Pronounced synergistic neuroprotective effect of GDNF and CNTF on axotomized retinal ganglion cells in the adult mouse. (November 2018) - Flachsbarth, Kai; Jankowiak, Wanda; Kruszewski, Katharina; Helbing, Sabine; Bartsch, Susanne; Bartsch, Udo
Abstract: Neuroprotection is among the potential treatment options for glaucoma and other retinal pathologies characterized by the loss of retinal ganglion cells (RGCs). Here, we examined the impact of a neural stem (NS) cell-based intravitreal co-administration of two neuroprotective factors on the survival of axotomized RGCs. To this aim we used lentiviral vectors to establish clonal NS cell lines ectopically expressing either glial cell line-derived neurotrophic factor (GDNF) or ciliary neurotrophic factor (CNTF). The modified NS cell lines were intravitreally injected either separately or as a 1:1 mixture into adult mice one day after an optic nerve lesion, and the number of surviving RGCs was determined in retinal flat-mounts two, four and eight weeks after the lesion. For the transplantation experiments, we selected a GDNF- and a CNTF-expressing NS cell line that promoted the survival of axotomized RGCs with a similar efficacy. Eight weeks after the lesion, GDNF-treated retinas contained 3.8- and CNTF-treated retinas 3.7-fold more RGCs than control retinas. Of note, the number of surviving RGCs was markedly increased when both factors were administered simultaneously, with 14.3-fold more RGCs than in control retinas eight weeks after the lesion. GDNF and CNTF thus potently and synergistically rescued RGCs from axotomy-induced cell death, indicating that combinatorial neuroprotective approaches represent a promising strategy to effectively promote the survival of RGCs under pathological conditions. Graphical abstract: Highlights: Lentivirally modified clonal neural stem (NS) cell lines stably overexpressed GDNF or CNTF. Grafted NS cells differentiated into astrocytes that survived in the vitreous cavity of a mouse optic nerve crush model. A grafted GDNF- and CNTF-expressing NS cell line promoted the survival of axotomized ganglion cells to a similar extent. A cell-based coadministration of GDNF and CNTF had a pronounced synergistic neuroprotective effect on injured ganglion cells.